The Role of the Cerebellum in Subsecond Time Perception: Evidence from Repetitive Transcranial Magnetic Stimulation - Lee, Kwang-Hyuk; Egleston, Paul N.; Brown, Wendy H.; Gregory, Abigail N.; Barker, Anthony T.; Woodruff, Peter W. R. (Journal of cognitive neuroscience, 2007)
In three experiments, we investigated the role of the cerebellum in sub- and suprasecond time perception by using repetitive transcranial magnetic stimulation (rTMS). In Experiment 1, subjects underwent four 8-min 1-Hz rTMS sessions in a within-subject design. rTMS sites were the medial cerebellum (real and sham rTMS), left lateral cerebellum, and right lateral cerebellum. Following each rTMS session, subjects completed a subsecond temporal bisection task (stimuli in the range 400–800 msec). Compared with sham rTMS, rTMS applied over the right lateral or medial cerebellum induced a leftward shift of the psychophysical function (perceived lengthening of time). In Experiment 2, a separate sample of subjects underwent the identical rTMS procedure and completed a suprasecond bisection task (stimuli in the 1000–2000 msec range). In this experiment, rTMS to the cerebellar sites did not produce any significant changes compared with sham rTMS. Experiment 3 employed a within-subject design to replicate findings from Experiments 1 and 2. Subjects underwent four rTMS conditions (sub- and suprabisection tasks following medial cerebellar and sham rTMS). rTMS induced a significant leftward shift of psychophysical function in the subsecond bisection, but not in the suprasecond bisection. In this study, we have demonstrated that transient cerebellar stimulation can differently affect the ability to estimate time intervals below and above a duration of 1 sec. The results of this study provide direct evidence for the role of the cerebellum in processing subsecond time intervals. This study further suggests that the perception of sub- and suprasecond intervals is likely to depend upon distinct neural systems.